2022
DOI: 10.1002/asl.1137
|View full text |Cite
|
Sign up to set email alerts
|

Future changes of the extreme high‐temperature events influenced by foehn winds in Niigata, Japan

Abstract: This study quantifies the future changes in extreme high-temperature events (ETE) influenced by foehn winds in Niigata, Japan, using numerical and sensitivity experiments based on regional climate modelling. Numerical simulations suggest that the contribution of foehn winds to ETEs is approximately 3.5 C in both the baseline (past) and future climate, and hence it remains unaffected by future climate change; however, the frequency of ETEs is influenced by foehn winds may increase by a factor of 1.5. This is du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Mizuta et al (2017) and Fujita et al (2019) have reported detailed experimental settings. Many previous studies have used d4PDF to reveal future projections of typhoons (Yoshida et al, 2017), heavy rain (Kitoh & Endo, 2019;Osakada & Nakakita, 2018), heavy snowfall (Kawase et al, 2016(Kawase et al, , 2020, and extremely high temperature (Ito et al, 2022;Nishi & Kusaka, 2022) in Japan.…”
Section: Datamentioning
confidence: 99%
“…Mizuta et al (2017) and Fujita et al (2019) have reported detailed experimental settings. Many previous studies have used d4PDF to reveal future projections of typhoons (Yoshida et al, 2017), heavy rain (Kitoh & Endo, 2019;Osakada & Nakakita, 2018), heavy snowfall (Kawase et al, 2016(Kawase et al, , 2020, and extremely high temperature (Ito et al, 2022;Nishi & Kusaka, 2022) in Japan.…”
Section: Datamentioning
confidence: 99%
“…FW usually occurs on the lee slope of mountain ranges, which experiences a localized form of air movement caused by a mountainous region [1]. FW occurs in many mountainous areas around the world, such as the Alps in Europe, the Rockies in America, and the Taihang Mountains in China [2][3][4][5][6][7][8][9][10][11][12][13][14]. It often poses a threat to local people's safety, the infrastructure, transportation, agricultural production, etc.…”
Section: Introduction 1foehn Wind (Fw)mentioning
confidence: 99%
“…Foehn wind is a type of downhill wind with high temperatures and low humidity and often occurs on the lee slope of mountain ranges due to the terrain forcing when airflow passes through a valley or mountain pass [1]. Foehn is very strong, seriously affecting the local weather and climate [2][3][4], as well as the local people's daily lives, transportation, agriculture, air quality, etc. In addition, the hot and dry foehn can also influence people's physical and mental health, which has attracted widespread attention [5][6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%